2004
DOI: 10.1097/00005650-200411000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Accuracy of Administrative Data in Health Information Systems

Abstract: Although more research is needed to evaluate the cause of inaccuracies and the relative contributions of patient, provider, and system level effects, it appears that significant inaccuracies in administrative data are common. Interventions aimed at correcting these errors appear feasible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
134
0
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 227 publications
(138 citation statements)
references
References 36 publications
2
134
0
2
Order By: Relevance
“…However, ICD-9 data are created for billing purposes and have a potential for selection bias, such as trend towards higher-paying diagnoses (17) and inaccuracies related to the procedure for creating the coding structure. (18).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…However, ICD-9 data are created for billing purposes and have a potential for selection bias, such as trend towards higher-paying diagnoses (17) and inaccuracies related to the procedure for creating the coding structure. (18).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Administrative data have multiple usespatient care, administrative functions, surveillance, and conducting of policy-relevant research, upon which decisions about population health and health services are made. 45 Efforts to address these gaps will increase our understanding of the strengths and limitations of these data for all their uses. …”
Section: Resultsmentioning
confidence: 99%
“…While there have been no specific reviews of ICD-9 code accuracy regarding FXS, SB, or MD in the United States, broader reviews of the literature reveal that unintentional coder errors caused by the limits of the clinician's knowledge and experience with the condition, misinterpreted information from the clinical record, and data entry mistakes lead to inaccuracy in ICD coding. [29][30][31] To control for miscoding, our inclusion criteria required two or more diagnoses of FXS, SB, or MD. The specification of at least two occurrences of a diagnosis was used in a Canadian study, which linked two surveillance systems; for spina bifida, they found an agreement rate of 64.1 %.…”
Section: Discussionmentioning
confidence: 99%